KEAP1–NRF2 system regulates age‐related spermatogenesis dysfunction - Sohei Kuribayashi; Shinichiro Fukuhara; Hiroaki Kitakaze; Go Tsujimura; Takahiro Imanaka; Koichi Okada; Norichika Ueda; Kentaro Takezawa; Kotoe Katayama; Rui Yamaguchi; Koichi Matsuda; Norio Nonomura (Reproductive Medicine and Biology)
Abstract Purpose The average fatherhood age has been consistently increasing in developed countries. Aging has been identified as a risk factor for male infertility. However, its impact on various mechanisms remains unclear. This study focused on the KEAP1–NRF2 oxidative stress response system, by investigating the relationship between the KEAP1–NRF2 system and age‐related changes in spermatogenesis. Methods For examination of age‐related changes, we used 10‐, 30‐, 60‐, and 90‐week‐old mice to compare sperm count, sperm motility, and protein expression. For assessment of Keap1 inhibition, 85‐week‐old C57BL/6J mice were randomly assigned to the following groups: control and bardoxolone methyl (KEAP1 inhibitor). Whole‐exome sequencing of a Japanese cohort of patients with non‐obstructive azoospermia was performed for evaluating. Results Sperm count decreased significantly with aging. Oxidative stress and KEAP1 expression in the testes were elevated. Inhibition of KEAP1 in aging mice significantly increased sperm count compared with that in the control group. In the human study, the frequency of a missense‐type SNP (rs181294188) causing changes in NFE2L2 (NRF2) activity was significantly higher in patients with non‐obstructive azoospermia than in healthy control group. Conclusions The KEAP1–NRF2 system, an oxidative stress response system, is associated with age‐related spermatogenesis dysfunction.